SOLUTION TUTO Dan Misc C4 - CONICS 21 - 22
SOLUTION TUTO Dan Misc C4 - CONICS 21 - 22
SOLUTION TUTO Dan Misc C4 - CONICS 21 - 22
ANSWER SCHEME
1 a) C (3, 0); r = 3
Equation of circle,
(x – 3)2 + (y – 0)2 = 32
x2 – 6x + 9 + y2 = 9
x2 + y2 – 6x = 0
b) x 2 + y 2 + 2 gx + 2 fy + c = 0
2 2
(1, 8) : (1) + (8) + 2 g (1) + 2 f (8) + c = 0
2 g + 16 f + c = −65 (1)
2 2
(-6, 1) : (−6) + (1) + 2 g (−6) + 2 f (1) + c = 0
− 12 g + 2 f + c = −37 (2)
2 2
(-2, -1) : (−2) + (−1) + 2 g (−2) + 2 f (−1) + c = 0
− 4 g − 2 f + c = −5 (3)
(1) – (2) : 14 g + 14 f = −28
g + f = −2 (4)
(3) – (2) : 8 g − 4 f = 32
2g − f = 8 (5)
(4) : 2 + f = −2 ⇒ f = −4
x 2 + y 2 + 2 gx + 2 fy + c = 0
c=0
1
SM025 CHAPTER 4: CONICS
2 2
(6, 0) : (6) + (0) + 2 g (6) + 2 f (0) = 0
36 + 12 g = 0
12 g = −36
g = −3
2 2
(0, -4) : (0) + (−4) + 2(−3)(0) + 2 f (−4) = 0
16 + 0 − 8 f = 0
f =2
x 2 + y 2 − 6x + 4 y = 0
d) x 2 + y 2 + 2 gx + 2 fy + c = 0
2 2
(1, 3) : (1) + (3) + 2 g (1) + 2 f (3) + c = 0
2 g + 6 f + c = −10 (1)
2 2
(-1, 1) : (−1) + (1) + 2 g (−1) + 2 f (1) + c = 0
− 2 g + 2 f + c = −2 (2)
The centre (− g ,− f ) lie on the line x + 2 y = 1
− g − 2 f =1 (3)
(1) – (2) : 4 g + 4 f = −8
g + f = −2 (4)
(3) + (4) : − f = −1 ⇒ f =1
(4) : g + 1 = −2 ⇒ g = −3
x 2 + y 2 + 2(−3) x + 2(1) y − 10 = 0
x 2 + y 2 − 6 x + 2 y − 10 = 0
e)
2
SM025 CHAPTER 4: CONICS
(-3,4)
4
4
(-3,-4)
C (-3, 4); r = 4
Equation of circle,
(x + 3)2 + (y – 4)2 = 42
x2 + 6x + 9 + y2 – 8y + 16 = 16
x2 + y2 + 6x – 8y + 9 = 0
C (-3, -4); r = 4
Equation of circle,
(x + 3)2 + (y + 4)2 = 42
x2 + 6x + 9 + y2 + 8y + 16 = 16
x2 + y2 + 6x + 8y + 9 = 0
f) C (-6, -6) , r = 6
Equation of circle,
6
(x + 6)2 + (y + 6)2 = 62
x2 + 12x + 36 + y2 + 12y + 36 = 36
x2 + y2 + 12x + 12y + 36 = 0
2) x 2 + y 2 + 2 gx + 2 fy + c = 0
2 2
(-1, 0) : (−1) + (0) + 2 g (−1) + 2 f (0) + c = 0
− 2 g + c = −1 (1)
2 2
(-1, 4) : (−1) + (4) + 2 g (−1) + 2 f (4) + c = 0
− 2 g + 8 f + c = −17 (2)
The centre (− g ,− f ) lie on the line 2 x + y = 4
3
SM025 CHAPTER 4: CONICS
− 2g − f = 4 (3)
(2) – (1) : 8 f = −16 ⇒ f = −2
(3) : − 2 g − (−2) = 4 ⇒ g = −1
(1) : − 2(−1) + c = −1 ⇒ c = −3
centre, C (− g ,− f ) = C (1,2)
2 2
radius, r = (−1) + (−2) − (−3) = 8 = 2 2
A (-1,4)
C(1,2)
(-1,0)
B
4−2 2
m AC = = = −1
−1−1 − 2
2−0 2
m BC = = =1
1+1 2
m AB × m BC = −1 × 1 = −1
3) x 2 + y 2 − 3x + 5 y − 4 = 0 (1)
2 2
x + y − x + 4y − 7 = 0 (2)
(2) – (1) : 2 x − y − 3 = 0
y = 2x − 3 (3)
Substitute (3) into (1) :
4
SM025 CHAPTER 4: CONICS
x 2 + (2 x − 3) 2 − 3 x + 5(2 x − 3) − 4 = 0
x 2 + 4 x 2 − 12 x + 9 − 3 x + 10 x − 15 − 4 = 0
5 x 2 − 5 x − 10 = 0
x2 − x − 2 = 0
( x − 2)( x + 1) = 0
x = 2 , x = −1
For x = 2 , y = 2(2) − 3 = 1
For x = −1 , y = 2(−1) − 3 = −5
The points of intersection are (2, 1) and (-1, -5)
2 2
4 a) x + y − 4 x + 6 y − 12 = 0
( x − 2) 2 − (−2) 2 + ( y + 3) 2 − (3) 2 − 12 = 0
( x − 2) 2 + ( y + 3) 2 = 5 2
centre , C (2 , − 3)
radius, r = 5
b) 3 x + 4 y = k
3x + 4 y − k = 0
3(2) + 4(−3) − k
d=
32 + 4 2
−6−k
d=
5
c) The line is tangent to circle
−6−k
=5
5
− 6 − k = 25
− 6 − k = 25 or − 6 − k = −25
k = −31 or k = 19
5
SM025 CHAPTER 4: CONICS
1
− 2x − y +1= 0
2
4x + y − 2 = 0
y = −4 x + 2
mT = −4
1
mN =
4
Equation of normal required
1
y − (−2) = ( x − 1)
4
4y + 8 = x −1
x − 4y − 9 = 0
2 2
1 1
2 2
[( x + 1) − (1) ] + y + − −4=0
2 2
2
2 1 1
( x + 1) − 1 + y + − − 4 = 0
2 4
2 2
1 21
( x + 1) + y + =
2
2 2
1
C − 1 , − r = 21
2 , 2
2
2 1 2 169
AC = (−1 − 5) + − − 2 =
2 4
2
169 21
= − = 37
d= AC 2 − r 2 4 2
6 a) x − 2y − 5 = 0 (1)
3x − y = 0
y = 3x (2)
Substitute (2) into (1)
x − 2(3 x) − 5 = 0
6
SM025 CHAPTER 4: CONICS
− 5x = 5
x = −1
(1) : y = 3(−1) = −3
∴ P (−1, −3)
b) The centre C (h, k ) lie on the line 2 x + y = 0
2h + k = 0 ⇒ k = −2h
C (h,−2h)
The shortest distance of CP
3(h) − (−2h)
(h + 1) 2 + (−2h + 3) 2 =
3 2 + (−1) 2
5
h 2 + 2h + 1 + 4h 2 − 12h + 9 = h 2
2
5 2
h − 10h + 10 = 0
2
h 2 − 4h + 4 = 0
(h − 2) 2 = 0
h=2
C (2,−4)
r = (2 + 1) 2 + (−4 + 3) 2 = 10
( x − 2) 2 + ( y + 4) 2 = ( 10 ) 2
x 2 − 4 x + 4 + y 2 + 8 y + 16 = 10
x 2 + y 2 − 4 x + 8 y + 10 = 0
c) A(7,1)
AC = (2 − 7) 2 + (−4 − 1) 2 = 50 > r
So, (7,1) is outside of the circle
The length of a tangent line required
d = AC 2 − r 2 = 50 − 10 = 40 = 2 10
( x − 1) 2 ( y − 2) 2
+ =1
7 a) 16 25
( x − h) 2 ( y − k ) 2
+ =1
a2 b2
h = 1, k = 2, a = 4 , b = 5
7
SM025 CHAPTER 4: CONICS
C (h , k ) = C (1 , 2)
V1 (h , k + b) = V1 (1 , 7)
V2 (h , k − b) = V2 (1, − 3)
c 2 = b 2 − a 2 = 25 − 16 = 9
c=3
F1 (h, k + c) = F1 (1 , 5)
F2 (h, k − c) = F2 (1,− 1)
Length of major axis = 2b = 10
Length of minor axis = 2a = 8
( x + 2) 2 ( y − 3) 2
+ =1
b) 25 9
( x − h) 2 ( y − k ) 2
+ =1
a2 b2
h = −2 , k = 3, a = 5 , b = 3
C (h , k ) = C (−2 , 3)
V1 (h + a , k ) = V1 (3 , 3)
V2 (h − a , k ) = V2 (−7 , 3)
c 2 = a 2 − b 2 = 25 − 9 = 16
c=4
F1 (h + c, k ) = F1 (2 , 3)
F2 (h − c, k ) = F2 (−6 , 3)
Length of major axis = 2a = 10
Length of minor axis = 2b = 6
2 2
c) x + 4 y − 6 x + 8 y = 1
( x − 3) 2 − 9 + 4( y 2 + 2 y ) = 1
( x − 3) 2 + 4( y + 1) 2 = 14
( x − 3) 2 ( y + 1) 2
+ =1
14 7
2
2
( x − h) ( y − k)2
+ =1
a2 b2
7
h = 3 , k = −1, a = 14 , b =
2
8
SM025 CHAPTER 4: CONICS
C (h, k ) = C (3,−1)
V1 (h + a , k ) = V1 (3 + 14 , − 1)
V2 (h − a , k ) = V2 (3 − 14 , − 1)
7 21
c 2 = 14 − =
2 2
21
c=
2
21
F1 (h + c, k ) = F1 (3 + , − 1)
2
21
F2 (h − c, k ) = F2 (3 − , − 1)
2
Length of major axis = 2a = 2 14
7
= 2b = 2 = 14
Length of minor axis 2
8) F1 (h, k + c) = F1 (−1, 6)
F2 (h, k − c) = F2 (−1, 0)
h = −1
k +c=6 (1)
k −c=0 (2)
(1) + (2) : 2k = 6
k =3
(1) : 3 + c = 6 ⇒ c = 3
2b = 10 ⇒ b = 5
c2 = b2 − a2
9 = 25 − a 2
a 2 = 16
( x − h) 2 ( y − k ) 2
+ =1
a2 b2
( x + 1) 2 ( y − 3) 2
+ =1
16 25
V(-1,8)
F(-1,6) 9
C(-1,3)
F(-1,0)
SM025 CHAPTER 4: CONICS
V(-1,-2)
9) C (h , k ) = C (−4 , 3)
h = −4 , k = 3
2a = 8 ⇒ a = 4
2b = 4 ⇒ b = 2
( x − h) 2 ( y − k ) 2
+ =1
a2 b2
( x + 4) 2 ( y − 3) 2
+ =1
16 4
2
10 a) ( x − h) = 4 p ( y − k )
V (h, k ) = V (3,2)
h = 3, k = 2
F (h, k + p ) = F (3,5)
p=3
( x − 3) 2 = 4(3)( y − 2)
( x − 3) 2 = 12( y − 2)
b) Directrix : y = 4
Directrix : y = k − p
k − p=4 (1)
( x − h) 2 = 4 p ( y − k )
F (h, k + p ) = F (0,−4)
h=0
k + p = −4 (2)
(1) + (2) : 2k = 0
10
SM025 CHAPTER 4: CONICS
k =0
(2) : p = −4
( x − 0) 2 = 4(−4)( y − 0)
x 2 = −16 y
11 a) y2 – 4y – 6x = 8
( y − 2) 2 − (−2) 2 − 6 x = 8
(y – 2)2 = 6x + 12
(y – 2)2 = 6(x + 2)
(y – k)2 = 4p(x – h)
3
p=
h = −2 , k = 2 , 2
V (h, k) = V (-2, 2)
1
−
F (h + p, k) = F ( 2 , 2)
7
−
Directrix, x = h – p = 2
1
−
V( -2,2) F ( 2 , 2)
O x
7
x=−
2
11
SM025 CHAPTER 4: CONICS
2
b) ( x + 2) = 6( y − 4)
( x − h) 2 = 4 p ( y − k )
3
⇒ h = −2, k = 4, p =
2
V (h , k ) = V (−2 , 4)
11
F (h , k + p ) = F (−2 , )
2
Directrix, y = k − p
5
y=
2
11
F (−2 , )
2
V(-2,4)
5
y=
2
0
12 a) B
A
y – x - 2=0
x 2 + y 2 − 8 x + 4 y − 14 = 0 (1)
y−x−2=0
y=x+2 (2)
Substitute (2) into (1) :
x 2 + ( x + 2) 2 − 8 x + 4( x + 2) − 14 = 0
x 2 + x 2 + 4 x + 4 − 8 x + 4 x + 8 − 14 = 0
12
SM025 CHAPTER 4: CONICS
2x 2 − 2 = 0
x2 = 1
x = 1 or x = −1
For x = 1 , y = 1 + 2 = 3
For x = −1 , y = −1 + 2 = 1
A(-1, 1), B(1, 3)
The equation of the tangent at A(-1, 1)
xx1 + yy1 − 4( x + x1 ) + 2( y + y1 ) − 14 = 0
x(−1) + y (1) − 4( x − 1) + 2( y + 1) − 14 = 0
− 5x + 3 y − 8 = 0 (3)
The equation of tangent at B(1, 3)
x(1) + y (3) − 4( x + 1) + 2( y + 3) − 14 = 0
− 3 x + 5 y − 12 = 0
3 x + 12
y=
5 (4)
Substitute (4) into (3) :
3 x + 12
− 5 x + 3 −8=0
5
− 25 x + 9 x + 36 − 40 = 0
− 16 x = 4
1
x=−
4
1
3 − + 12
4 9
y= =
(4) : 5 4
−1 9
,
Intersection point is 4 4
−1+1 1+ 3
V (h , k ) = V , =
b) 2 2 V (0,2)
( x − h) 2 = 4 p ( y − k )
x 2 = 4 p ( y − 2)
1
2 p=
At B(1, 3) : 1 = 4 p (3 − 2) ⇒ 4
1
x 2 = 4 ( y − 2)
4
13
SM025 CHAPTER 4: CONICS
x2 = y − 2
9
F (h, k + p ) = F (0, )
4
1) A (2,0) , B (10,4)
2 + 10 0 + 4
a) C (h, k ) = , = (6,2)
2 2
r = (6 − 2) 2 + (2 − 0) 2 = 20
Equation of circle
( x − 6) 2 + ( y − 2) 2 = 20
x 2 − 12 x + 36 + y 2 − 4 y + 4 = 20
x 2 + y 2 − 12 x − 4 y + 20 = 0
b) B (10, 4)
4−2 1
m BC = =
10 − 6 2
mT = −2
Equation of tangent required
y − 4 = −2( x − 10)
y = −2 x + 24
( x − h) 2 ( y − k ) 2
2) + =1
a2 b2
C (h, k ) = C (0,0)
h = 0, k = 0
x2 y2
+ =1
a2 b2
(0) 2 (3) 2
(0, 3) : 2 + 2 = 1 ⇒ b = 3
a b
2
(1) (1) 2 9
(1, 1) : 2 + = 1 ⇒ a2 =
a 9 8
14
SM025 CHAPTER 4: CONICS
x2 y2
+ =1
9 9
8
9
c2 = b2 − a2 = 9 −
8
63
c=
8
63
F1 (h, k + c) = F1 (0 , )
8
63
F2 (h, k − c) = F2 (0 , − )
8
3 a) C1 : x 2 + y 2 − 2 x − 2 y + 1 = 0 (1)
2 2 2 2
( x − 1) − (−1) + ( y − 1) − (−1) + 1 = 0
( x − 1) 2 + ( y − 1) 2 = 12
centre , C (1, 1)
radius, r = 1
b) C 2 : x 2 + y 2 = 1 (2)
Equation of tangent,
At (0,3), 3 = 𝑚𝑚(0) + 𝑐𝑐
𝑐𝑐 = 3
y = mx + 3 (3)
Substitute (3) into (2)
x 2 + (mx + 3) 2 = 1
x 2 + m 2 x 2 + 6mx + 9 = 1
(m 2 + 1) x 2 + 6mx + 8 = 0
Since is tangent line
(6m) 2 − 4(m 2 + 1)(8) = 0
36m 2 − 32m 2 − 32 = 0
4m 2 − 32 = 0
m2 = 8
m = 2 2 or m = −2 2
y = 1− x (5)
Substitute (4) into (2)
x 2 + (1 − x) 2 = 1
x 2 + 1 − 2x + x 2 = 1
2x 2 − 2x = 0
2 x( x − 1) = 0
x = 0 or x = 1
For x = 0 , y = 1
For x = 1 , y = 0
The circle pass through the points (0, 1), (1, 0) and (-5, 0)
x 2 + y 2 + 2 gx + 2 fy + c = 0
(0, 1) : (0) 2 + (1) 2 + 2 g (0) + 2 f (1) + c = 0
2 f + c = −1 (5)
(1, 0) : (1) 2 + (0) 2 + 2 g (1) + 2 f (0) + c = 0
2 g + c = −1 (6)
2 2
(-5, 0) : (−5) + (0) + 2 g (−5) + 2 f (0) + c = 0
− 10 g + c = −25 (7)
(6) –(7) : 12 g = 24
g=2
(6) : 2(2) + c = −1
c = −5
(5) : 2 f + (−5) = −1
f =2
2 2
x + y + 2(2) x + 2(2) y + (−5) = 0
x 2 + y 2 + 4x + 4 y − 5 = 0
4) x 2 + y 2 + 2 gx + 2 fy + c = 0
(1, 4) : (1) 2 + (4) 2 + 2 g (1) + 2 f (4) + c = 0
2 g + 8 f + c = −17 (1)
(2, 2) : (2) + (2) 2 + 2 g (2) + 2 f (2) + c = 0
2
4 g + 4 f + c = −8 (2)
(-1, 3) : (−1) + (3) 2 + 2 g (−1) + 2 f (3) + c = 0
2
− 2 g + 6 f + c = −10 (3)
(2) – (1) : 2g − 4 f = 9 (4)
(3) – (1) : − 4g − 2 f = 7 (5)
(5) × 2 : − 8 g − 4 f = 14 (6)
(4) – (6) : 10 g = −5
1
g=−
2
16
SM025 CHAPTER 4: CONICS
1
(4) : 2 − − 4 f = 9
2
5
f =−
2
1 5
(1) : 2 − + 8 − + c = −17
2 2
c=4
1 5
x 2 + y 2 + 2 − x + 2 − y + 4 = 0
2 2
2 2
x + y − x − 5y + 4 = 0
2 2 2 2
1 1 5 5
x − − − + y − − − + 4 = 0
2 2 2 2
2 2
1 1 5 25
x − − +y − − +4=0
2 4 2 4
2 2
1 5 10
x − +y − − =0
2 2 4
2 2
1 5 5
x − +y − =
2 2 2
2 2 2
1 5 5
x − + y − =
2 2 2
5
radius , r =
2
5 a) r = (3 − 0) 2 + (−3 − 0) 2 = 18
( x − 3) 2 + ( y + 3) 2 = ( 18 ) 2
x 2 − 6 x + 9 + y 2 + 6 y + 9 = 18
x 2 + y 2 − 6x + 6 y = 0
b) x 2 + y 2 − 6 x + 6 y = 0 (1)
y = x−6 (2)
Substitute (2) into (1)
x 2 + ( x − 6) 2 − 6 x + 6( x − 6) = 0
x 2 + x 2 − 12 x + 36 − 6 x + 6 x − 36 = 0
2 x 2 − 12 x = 0
2 x( x − 6) = 0
x = 0 or x = 6
For x = 0 , y = −6
17
SM025 CHAPTER 4: CONICS
For x = 6 , y = 0
P (0 , − 6) , Q(6 , 0)
c) y = x + c (3)
Substitute (3) into (1)
x 2 + ( x + c) 2 − 6 x + 6( x + c) = 0
x 2 + x 2 + 2cx + c 2 − 6 x + 6 x + 6c = 0
2 x 2 + 2cx + c 2 + 6c = 0
Since is tangent line
(2c) 2 − 4(2)(c 2 + 6c) = 0
4c 2 − 8c 2 − 48c = 0
− 4c 2 − 48c = 0
− 4c(c + 12) = 0
c = 0 or c = −12
(3) : y = x or y = x − 12
For y = x
(1) : x 2 + x 2 − 6 x + 6 x = 0
2x 2 = 0
x=0
y=0
A( 0, 0)
For y = x − 12
(1) : x 2 + ( x − 12) 2 − 6 x + 6( x − 12) = 0
x 2 + x 2 − 24 x + 144 − 6 x + 6 x − 72 = 0
2 x 2 − 24 x + 72 = 0
x 2 − 12 x + 36 = 0
( x − 6) 2 = 0
x=6
y = −6
B(6, -6)
6) 4 x 2 − 16 x + y 2 + 2 y − 8 = 0
4( x 2 − 4 x) + y 2 + 2 y − 8 = 0
4[( x − 2) 2 − 2 2 ] + [( y + 1) 2 − 12 ] − 8 = 0
4( x − 2) 2 − 16 + ( y + 1) 2 − 1 − 8 = 0
4( x − 2) 2 + ( y + 1) 2 = 25
( x − 2) 2 ( y + 1) 2
+ =1
25 25
4
18
SM025 CHAPTER 4: CONICS
( x − h) 2 ( y − k ) 2
+ =1
a2 b2
5
a= , b=5
2
b>a
This is an ellipse with vertical major axis.
h = 2 , k = −1
C (h, k ) = C (2,−1)
25 75
c 2 = b 2 − a 2 = 25 − =
4 4
75 5
c= = 3
4 2
5
F1 (h, k + c) = F1 (2,−1 + 3)
2
5
F2 (h, k − c) = F2 (2,−1 − 3)
2
2−0
c) m1 = =2
1− 0
m1 m2 = −1
1
m2 = −
2
19
SM025 CHAPTER 4: CONICS
Equation of chord
1
y − 0 = − ( x − 0)
2
1
y=− x (2)
2
Substituting (2) into (1) :
2
1 1
x 2 + − x − 2 x − 4 − x − 3 = 0
2 2
1
x 2 + x 2 − 2x + 2x − 3 = 0
4
5 2
x =3
4
12
x2 =
5
3 3
x=2 or x = −2
5 5
3 1 3 3
when x = 2 , y = − 2 = −
5 2 5 5
3 1 3 3
when x = −2 , y = − − 2 =
5 2 5 5
3 3 3 3
The points of intersection are 2 ,−
,
− 2
, .
5 5 5 5
8) x 2 + y 2 + 2 x = 4
( x + 1) 2 − (1) 2 + y 2 = 4
( x + 1) 2 + y 2 = 5
C (−1, 0) , r = 5
x 2 + y 2 + 2x − 4 = 0
x 2 + y 2 + 2 gx + 2 fy + c = 0
2𝑔𝑔 = 2; g = 1 ,
2 f = 0 , 𝑓𝑓 = 0 c = −4 , x1 = 0 ; y1 = 2
Equation of tangent required
xx1 + yy1 + g ( x + x1 ) + f ( y + y1 ) + c = 0
x(0) + y (2) + 1( x + 0) + 0( y + 2) − 4 = 0
2y + x − 4 = 0
9 a) x 2 − 4 x − 4 y + 8 = 0
20
SM025 CHAPTER 4: CONICS
( x − 2) 2 − (−2) 2 = 4 y − 8
( x − 2) 2 = 4 y − 4
( x − 2) 2 = 4( y − 1)
( x − h) 2 = 4 p ( y − k )
h = 2 , k = 1, p = 1
V (h , k ) = V (2 ,1)
F (h , k + p ) = F (2 , 2)
Directrix : y = k − p
y = 1−1
y=0
dy
b) 2 x − 4 − 4 =0
dx
dy
4 = 2x − 4
dx
dy 1
= x −1
dx 2
1
At A(-2, 5), m A = (−2) − 1 = −2
2
5 1 1
At B 3, , m B = (3) − 1 =
4 2 2
1
m A m B = (−2) = −1
2
The tangent lines to the parabola at A and B intersect at the right angle.
(0 − h ) 2 + (0 − k ) 2 = 5 2
h 2 + k 2 = 25 (2)
Substitute (1) into (2):
h 2 + (1 − h) 2 = 25
h 2 + 1 − 2h + h 2 = 25
2h 2 − 2h − 24 = 0
h 2 − h − 12 = 0
(h + 3)(h − 4) = 0
h = −3 or h = 4
21
SM025 CHAPTER 4: CONICS
For h = −3
(1) : k = 1 − (−3) = 4
For h=4
(1) : k = 1 − (4) = −3
( x − h) 2 + ( y − k ) 2 = r 2
11) 9 x 2 − 72 x + 16 y 2 + 32 y = −16
a) 9[ x 2 − 8 x] + 16[ y 2 + 2 y ] = −16
9[( x − 4) 2 − (−4) 2 ] + 16[( y + 1) 2 − (1) 2 ] = −16
9( x − 4) 2 − 144 + 16( y + 1) 2 − 16 = −16
9( x − 4) 2 + 16( y + 1) 2 = 144
( x − 4) 2 ( y + 1) 2
+ =1
16 9
b) ( x − h) 2 ( y − k ) 2
+ =1
a2 b2
h = 4 , k = −1 , a = 4 , b = 3 , a > b
c2 = a2 − b2
c 2 = 4 2 − 32
c= 7
F1 (h + c , k ) = F1 (4 + 7 , − 1 )
F2 (h − c , k ) = F2 (4 − 7 , − 1 )
V1 (h + a , k ) = V1 (8 , − 1 )
V2 ( h − a , k ) = V 2 (0 , − 1 )
∴ Length of major axis = 2a = 2(4) = 8
∴ Length of minor axis = 2b = 2(3) = 6
22
SM025 CHAPTER 4: CONICS
c) C (h , k ) = C (4 , − 1)
y2
x
V2 F2 C F1 V1
23
SM025 CHAPTER 4: CONICS
2 7
− 2 g + 4 − − = −5
3 3
8 7
− 2 g − − = −5
3 3
− 2 g − 5 = −5
− 2g = 0
g =0
Center of circle,
C = ( − g ,− f )
2
= − 0,− −
3
2
= 0,
3
−5+3 2+ 2
Centre , C (h, k ) = ,
2 2
2 4
= − ,
2 2
= (−1 ,2 )
24
SM025 CHAPTER 4: CONICS
(b) y
(-1, 6)
x
(-1, 2)
𝐹𝐹1 (−5, 2) x
x x 𝐹𝐹2 (3, 2)
14. ,
a) Equation of circle
25
SM025 CHAPTER 4: CONICS
b)
Equation of tangent
c)
or
d)
15 a)
b) , , ,
26
SM025 CHAPTER 4: CONICS
C: (1,-3) 𝑎𝑎 = 1 & 𝑏𝑏 = 3
Point of intersection:
(1,0) : 𝑦𝑦 = 𝑚𝑚𝑚𝑚 + 𝑐𝑐
0+1
𝑚𝑚𝑛𝑛 = 1−2 = −1, ∴ 𝑚𝑚𝑡𝑡 = 1
0 = 1(1) + 𝑐𝑐, 𝑐𝑐 = −1 ∴ 𝑦𝑦 = 𝑥𝑥 − 1
(3,0) : 𝑦𝑦 = 𝑚𝑚𝑚𝑚 + 𝑐𝑐
0+1
𝑚𝑚𝑛𝑛 = 3−2 = 1, ∴ 𝑚𝑚𝑡𝑡 = −1
0 = −1(3) + 𝑐𝑐, 𝑐𝑐 = 3 ∴ 𝑦𝑦 = 𝑥𝑥 + 3
27
SM025 CHAPTER 4: CONICS
𝑥𝑥 − 1 = −𝑥𝑥 + 3
2𝑥𝑥 = 4, 𝑥𝑥 = 2 ∴ 𝑦𝑦 = 2 − 1 = 1
Therefore (2,1) point of intersection
28